Left ventricular assist device implantation in patients with a history of malignancy. Issue 9 (27th July 2020) - Hong, Yeahwa; Seese, Laura; Hickey, Gavin; Chen, Shangzhen; Mathier, Michael A.; Kilic, Arman
Abstract: Background: This study evaluates the impact of a history of malignancy on outcomes of left ventricular assist device (LVAD) implantation. Methods: Adult patients with a preimplant history of malignancy who underwent LVAD implantation between 2006 and 2018 were included. The primary outcome was post‐LVAD survival. Results: A total of 250 patients underwent LVAD implant during the study period, including 37 (14.8%) patients with a history of malignancy. Of these 37 patients, five (13.5%) had active malignancy at the time of LVAD implantation, and seven had more than one type of cancer. The median disease‐free duration before LVAD was 3.5 years (interquartile range [IQR] 1.0‐7.75 years). The most common types of malignancy included urologic (n = 20; 45.5%), skin (n = 7, 15.9%), and leukemia or lymphoma (n = 6; 13.6%). Median follow‐up was 244 (IQR, 126‐571) days and 313 (IQR 127‐738) days for those with and without a history of malignancy, respectively ( P  = .49). Unadjusted post‐LVAD survival was reduced in those with a malignancy history (2‐year survival 53.4% vs 66.9%; P  = .01), a finding that persisted after risk‐adjustment (hazard ratio 1.89, 95% confidence interval, 1.13‐3.14; P  = .01). Only one (2.7%) patient died post‐LVAD from their cancer. Conclusions: Although a history of malignancy is associated with reduced survival after LVAD implantation, more than half of the patients are alive at 2 years. This combined with the fact that most do not die from causes directly related to their cancer suggest that LVAD implantation is reasonable to perform in carefully selected patients with a history of malignancy.